Estimation of Water Losses Through Evapotranspiration of Water Hyacinth (Eichhornia crassipes) - Dilyan Sasaqi; Pranoto Pranoto; Prabang Setyono (Universitas Sebelas Maret, 2019)
Batujai Reservoir locates in Batujai Village, Praya Barat, Central Lombok, West Nusa Tenggara. It is the primary source of irrigation water supply for agriculture in Central Lombok District with an area of around 3,235 ha. The problem is the bloom of water hyacinth weed (Eichhornia crassipes), which can cause reservoir water loss through evapotranspiration, affecting the amount of water reservoir available for the dry season. The objective was to identify the area of cover and estimate water loss through water hyacinth evapotranspiration for the period 2013 – 2017. This study used a descriptive method by analysis of secondary data which were meteorological data and landsat-8 satellite imagery. Evapotranspiration analyzes use CROPWAT 8.0, monitoring water hyacinth cover using landsat–8 satellite imagery processed using ENVI 5.3 and ArcGIS 10.4 software. The results show that the spatial distribution of water hyacinth can be detected and mapped accurately with an overall classification accuracy of 84.11% – 97.04% using Landsat 8 data, with a kappa coefficient of 0.80 – 0.96. The area of water hyacinth cover ranges from 38,400 m2 – 2,158,500 m2, with a cover area of more than 20%, causing water loss above 8,000 m3 day-1, which occurred in April 2013, April 2015, April 2016, February 2015, May 2014, May 2016 and July 2016, in those months it was seen that the amount of water loss was greater. Therefore, it is needed to suppress the growth of water hyacinth, in maintaining reservoir water storage capacity to support a systems of sustainable agriculture.